Essa moça tá diferente: debates sobre a representação da sexualidade feminina - Carlos Wagner Jota Guedes (2006)
The present work looks for understanding the changes occurred in the sexual and affective careers of psychologized and intellectualized women in contemporary western society. Essentially, these changes happen as a product of transformations in modern society, which, through feminism, medical-pharmaceutic control of reproduction, female work and education, civil rights and the relativization of sexual roles directed to men and women, were effected. These changes are characterized by the convergence in the age of the first sexual relation between men and women, by the singular importance of prenuptial sexuality, by the increase of maternities without marriage, by the declination of birth rates and formal marriages, by the diffusion of new sexual practices, among others. Above all, these transformations affect male and female meanings, as well as the ones of man and woman. Although it is still present, in contemporariness, in the womans double identity, like a saint or like a whore, it lies clouded by sexual and affective practices that contrast with traditional models. Therefore, through bibliographic review, one seeks to indicate the processes that constitute these transformations in contemporary society. Transformations that accompany the crescent debate in the Sciences, generally, and in Social Sciences, in particular, concerning sexuality, and the sexual gender and identity. In this context, essentialist and constructivist visions are in collision as hegemonic explanatory model. The constructivist perception was chosen. Thus, the comprehension of the processes that configure the social representations over the constituted sexual roles about the sexual difference becomes necessary. Both sanctity and perdition lie that way, guided by notions of what masculine and feminine are, and its consequent obsession about what is the man and what is the woman. Passiveness and activeness concepts are, in this environment, components of the social representations upon sexual difference. At last, it is the interweaving of this duality that allows the existence of new sexual-affective careers to some women social sectors. Hence, a discourse of access to the more equalitarian pleasure for both sexes could be developed.